Peculiar Distribution of Tumorous Xanthomas in an Adult Case of Erdheim-Chester Disease Complicated by Atopic Dermatitis - Yukako Murakami; Mari Wataya-Kaneda; Mika Terao; Hiroaki Azukizawa; Hiroyuki Murota; Yukiko Nakata; Ichiro Katayama (Karger Publishers, 2011)
Erdheim-Chester disease is a rare non-Langerhans form of histiocytosis with multiple organ involvement. Approximately 20% of patients have xanthoma-like lesions, usually on the eyelids. We report a case of Erdheim-Chester disease in a 32-year-old male who showed peculiar xanthomatous skin lesions and also had atopic dermatitis. His skin manifestations included ring-like yellowish tumors on his periorbital regions, rope necklace-like tumors on his neck, and spindle-shaped tumors on his right preauricular region and cubital fossas. He also had exophthalmos and diabetes insipidus. Chronic eczematous lesions were present on the flexor aspect of his extremities, and his serum eosinophil numbers and immunoglobulin E levels were elevated. A histological examination of his right neck tumor showed foamy macrophages and touton-type giant cells, which were positive for CD68 and CD163 and negative for S-100 and CD1a. We suggest that the complication of atopic dermatitis may have contributed to the uncommon clinical features in this case.